State regulation distribution of false information in the media space: foreign experience - Gryn, Dmytro (Pressing Problems of Public Administration, 2022)
This paper focuses on necessity to regulate public relations regarding public figures related to defamation issues in the media space. The paper examines the experience of the countries in regulating defamatory content in the media space in general and in relation to public figures in particular.Results of this research are consistent with by the fact that a public figure is indeed limited in his right to respect for honor, dignity and business reputation, but is not deprived of such rights, which provides grounds for legislative consolidation of the protection of the honor, dignity and business reputation of a public figure from defamatory statements in the media space.This article established a connection between information activities on the Internet and defamation disputes regarding public figures. Such a connection consists in the presence in such information of public interest and, as a result, defamatory information causes public resonance.In the process of researching was established that national and European courts, considering each defamation case separately, developed certain conclusions that are guided by the resolution of defamation disputes regarding public figures.Using the example of countries such as Germany, Norway, France and Sweden, it was found that the way to settle disputed defamatory relations involving a public figure is to designate a public figure as a special subject of the said legal relations. In general, this research shows problems of the potential of the right to freedom of expression in the conditions of the functioning of the global Internet network, together with the need to timely regulate such social relations in the Internet network in order to protect the right of other persons to respect their honor, dignity and business reputation.Account the existing world experience, in article formulated recommendations on the regulation of public relations in order to reduce the level of defamation in the media space regarding public figures. With the adoption of the relevant legislative changes, the issue of defamatory content in the media space regarding public figures can be comprehensively resolved, and the relevant relations can be settled in a timely manner.